1995
DOI: 10.1071/sb9950085
|View full text |Cite
|
Sign up to set email alerts
|

An account of the red algal genus Sporolithon (Sporolithaceae, Corallinales) in southern Australia

Abstract: Sporolithon (Sporolithaceae, Corallinales) is represented in southern Australia by S. durum (Foslie) Townsend et Woelkerling, comb. nov. The species and the development of male and female-carposporangial conceptacles and tetrasporangial compartments and sori are described in detail for the first time. Information on etymology, collections examined, distribution, seasonality and habit and comparisons with other species is also included. Published records of S. erythraeum from southern Australia have not been su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 0 publications
3
62
0
Order By: Relevance
“…In S. episporum, the opposite is the case. However, the use of this feature has been contested by some authors (Townsend et al 1995, Harvey et al 2002. Harvey et al (2002) reported that the proportion of secondary pitconnections and cell fusion varies in specimens of S. durum found in Australia, and that this feature should not be used to separate the two species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. episporum, the opposite is the case. However, the use of this feature has been contested by some authors (Townsend et al 1995, Harvey et al 2002. Harvey et al (2002) reported that the proportion of secondary pitconnections and cell fusion varies in specimens of S. durum found in Australia, and that this feature should not be used to separate the two species.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens in this study were identified as S. episporum by satisfying the criteria set by Keats & Chamberlain (1993) and Nunes et al (2008) (Table 1). There have been few descriptions of the structure and development of the carposporangial conceptacles in Sporolithon, being restricted to S. durum (Foslie) Townsend & Woelkerling (1995: 86-91) (Townsend et al 1995, Woelkerling 1996, Harvey et al 2002 and S. episoredion (Adey, Townsend & Boykins) Verheij (1992: 501). S. episoredion has carposporangial conceptacles much larger than those found in the present study (Verheij 1992, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…According to modern concepts of coralline red algal taxonomy, these characters are no longer sufficient for precise identification because they are too variable (Verheij 1993;Bahia et al 2011). The most important characters currently used in Sporolithon taxonomy are: 1) diameter/length of the tetrasporangial compartment, 2) fate of old sporangial cases, 3) number of cells in the paraphyses, 4) Presence of a basal layer of elongated cells in areas where sporangia develop, (5) number of cells by which sorus is raised above surrounding thallus surface and (6) soral organization (Verheij 1993;Keats & Chamberlain 1993;Townsend et al 1995;Alongi et al 1996;Bahia et al 2011;Bahia et al 2013). In the present work we compared Sporolithon species for which recent (since 1990) detailed descriptions are available (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diagnostic features used in many taxonomic reviews (Verheij 1993;Keats & Chamberlain 1993;Townsend et al 1995;Alongi et al 1996;Bahia et al 2011;Bahia et al 2013) were used: 1) diameter/length of the tetrasporangial compartment, 2) fate of old sporangial cases, 3) number of cells in the paraphyses, 4) Presence of a basal layer of elongated cells in areas where sporangia develop, (5) number of cells by which sorus is raised above surrounding thallus surface and (6) soral organization. Identified samples were incorporated into the herbarium collection of the Botanical Garden of Rio de Janeiro (RB) and Museu Nacional (R).…”
Section: Laboratory Workmentioning
confidence: 99%
“…The terminology used in this paper is that used by Townsend and Adey (1990) and Townsend et al (1994Townsend et al ( , 1995 except that the term sorus is replaced by nemathecium. A nemathecium is defined as an area of thallus where the vegetative structure has been modified concurrent with the differentiation of reproductive cells.…”
Section: Methodsmentioning
confidence: 99%